Bacterial Community and Genomic Analysis of Carbapenem-Resistant Acinetobacter baumannii Isolates from the Environment of a Health Care Facility in the Western Region of Saudi Arabia - Muhammad Yasir; Abdullah Mohammad Subahi; Hani A. Shukri; Fehmida Bibi; Sayed Sartaj Sohrab; Maha Alawi; Anees A. Sindi; Asif A. Jiman-Fatani; Esam I. Azhar (MDPI AG, 2022)
The escalating transmission of hospital-acquired infections, especially those due to antimicrobial-resistant bacteria, is a major health challenge worldwide. In this study, a culturomic analysis of bacterial community in a tertiary care hospital in the western region of Saudi Arabia is performed using environmental samples. The genome sequencing of four Acinetobacter baumannii was performed on isolates recovered from an intensive care unit (ICU) environment and clinical samples. A total of 361 bacterial isolates from surface and air samples were identified by MALDI-TOF technique or 16S rRNA gene sequencing. The isolates were classified into 70 distinct species, including ESKAPE pathogens. Resistance in Gram-positive isolates was mainly found to be against benzylpenicillin, azithromycin, ampicillin, and trimethoprim/sulfamethoxazole. Carbapenem- and multidrug-resistant isolates of A. baumannii and Klebsiella pneumonia were found on the ICU surfaces. Genome sequencing revealed that the carbapenem-resistant A. baumannii isolate from ICU environment was linked with those of clinical origin. The isolate Ab133-HEnv was classified as a novel sequence type (ST2528) based on a new allele of Oxf_gdhB-286. Three beta-lactam-antibiotic-resistance genes, blaADC-25, blaOXA-23, and blaOXA-66, were found in most of the analyzed genomes. Collectively, the results of this study highlight the spread of antimicrobial-resistant nosocomial pathogens in a health care facility in Saudi Arabia.